2021
DOI: 10.3390/antiox10101508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Antioxidative and Hepatoprotective Activities of Dimethyl Diphenyl Bicarboxylate in Four Animal Models of Hepatic Injury

Abstract: As a well-known hepatoprotective and antioxidant agent, dimethyl diphenyl bicarboxylate (DDB) has frequently been employed to remedy various liver diseases. However, it is still uncertain whether DDB exerts consistent hepatoprotective and antioxidative activities against varying degrees of hepatic damage. Therefore, DDB (100, 25, 5, or 50 mg/kg depending on the model) was administered to animals in four representative models of liver injury (CCl4 chemical acute model, DMN subchronic model, TAA chronic model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…When a hepatic injury occurs, AST and ALT levels increase in the plasma because of release from the damaged hepatocyte cytoplasm. [ 44 ] The present results also showed that VCR significantly increased AST, ALT, and ALP levels. This is consistent with several studies that have shown the hepatic toxicity of VCR.…”
Section: Discussionsupporting
confidence: 77%
“…When a hepatic injury occurs, AST and ALT levels increase in the plasma because of release from the damaged hepatocyte cytoplasm. [ 44 ] The present results also showed that VCR significantly increased AST, ALT, and ALP levels. This is consistent with several studies that have shown the hepatic toxicity of VCR.…”
Section: Discussionsupporting
confidence: 77%
“…Peroxidation of membrane lipids leads also to the formation of reactive aldehydes such as 4-hydroxy-2nonenal (4HNE) and malondialdehyde (MDA) that are considered the major peroxidation's primary end-product of polyunsaturated fatty acids, which further aggravates the injury [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Alda-1 is an organic compound that improves the enzymatic activity of aldehyde dehydrogenase-2 (ALDH2), which in turn performs an important role in removing of endogenous aldehydes like 4HNE and MDA produced by lipid peroxidation provoked by oxidative stress [42,69] . Liver contains many mitochondria, due to their great amounts of membranes and unsaturated phospholipids, mitochondria are well known as a major generator of ROS and a target for lipid peroxidation [70] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduced serum albumin deduced that the extract of C. farinosa induced hypoalbuminemia in animals (Table . 3). Hypoalbuminemia is a sensitive indicator for liver dysfunction [32,33]. furthermore, the histopathological sections of the liver showed morphological characteristics of cell death which models hepatocyte apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%